Penerapan Restorative Justice Dalam Proses Penyidikan Tindak Pidana Penganiayaan - Asriadi Asriadi; Muhammad Natsir; Phireri Phireri (Jurnal Litigasi Amsir, 2024)
This study aims to analyze the factors that hinder the application of restorative justice in the investigation of violent crimes in the Barru Police. The method used is empirical research with a legislative approach and case studies. The results of the study show that the lack of agreement between the victim and the perpetrator is the main factor in the non-occurrence of restorative justice, where the victim prefers to continue the case to the court to get punishment for the perpetrator. In addition, victims often apply conditions that cannot be fulfilled by the perpetrator, such as rehabilitation costs. The application of restorative justice at the Barru Police is carried out through mediation between the perpetrator, the victim, and the victim's family, by involving neutral parties such as community leaders and religious leaders. This process follows the provisions in Peraturan Kapolri Nomor 8 Tahun 2021 tentang Penghentian Tindak Pidana Berdasarkan Keadilan Restoratif, and cases that are successfully resolved restoratively tend to be stable every year.